2018
DOI: 10.14203/beritabiologi.v17i2.3313
|View full text |Cite
|
Sign up to set email alerts
|

Karakterisasi Keragaman Genetik 27 Genotipe Cabai Berdasarkan Marka SSR (Simple Sequence Repeat)

Abstract: Chili pepper (Capsicum annuum) is one of the high economical horticultural comodity in Indonesia and its genetic diversity contributes to the success of breeding programs. Simple sequence repeat (SSR) markers can be used to analyze genetic diversity among chili pepper genotypes. The aim of this research was to analyze the genetic diversity of twenty-seven genotypes of chili pepper by using 24 SSR markers. The collected data was analyzed using cluster analysis and principle coordinate analysis (PCoA). The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…The individuals of pitcher plants showed an indication to form four groups. This shows that accessions located at one of the adjacent coordinates show a high level of genetic similarity (Terryana et al, 2018).…”
Section: Resultsmentioning
confidence: 81%
“…The individuals of pitcher plants showed an indication to form four groups. This shows that accessions located at one of the adjacent coordinates show a high level of genetic similarity (Terryana et al, 2018).…”
Section: Resultsmentioning
confidence: 81%
“…Overall, the varied degrees of resistance to anthracnose observed in the pepper varieties in our study could be supported by further molecular analysis Analysis of molecular marker polymorphisms. We successfully uncovered 14 loci across the 15 pepper ned an average number of 7 alleles with a range of 3 alleles to 5 alleles per locus (Table 4), which is a lower number than that reported in a previous study that identified 179 alleles in 27 red pepper genotypes using 24 microsatellite markers [17]. The number September 2019  Vol.…”
Section: Anthracnose Symptoms Visualizedmentioning
confidence: 72%
“…successfully uncovered 14 loci across the 15 pepper varieties. We obtained an average number of 7 alleles with a range of 3 alleles to 5 alleles per locus (Table 4), which is a lower number than that reported in a previous study that identified 179 alleles in 27 red pepper gen types using 24 microsatellite markers [17]. The n the dip method to understand the physical resistance ].…”
Section: Anthracnose Symptoms Visualizedmentioning
confidence: 87%
See 1 more Smart Citation
“…Pemanfaatan teknologi marka molekuler menghasilkan sidik jari DNA yang efektif dan efisien dalam mengidentifikasi varietas pada level DNA karena lebih akurat dan tidak dipengaruhi oleh faktor lingkungan (Risliawati et al 2015;Gao et al 2016). Marka molekuler juga telah banyak digunakan pada analisis diversitas genetik dengan presisi tinggi dan untuk memprediksi latar belakang genetik varietas (Ribeiro et al 2013;Lestari et al 2016;Terryana et al 2018). Di samping itu, marka molekuler dapat digunakan sebagai pelengkap pada uji kebaruan, keunikan, keseragaman, dan kestabilan (BUSS) melalui perbandingan profil sidik jari DNA.…”
unclassified